Share Issuance and Factor Timing - GREENWOOD, ROBIN; HANSON, SAMUEL G. (Journal of Finance, 2012)
ABSTRACT We show that characteristics of stock issuers can be used to forecast important common factors in stocks' returns such as those associated with book‐to‐market, size, and industry. Specifically, we use differences between the attributes of stock issuers and repurchasers to forecast characteristic‐related factor returns. For example, we show that large firms underperform after years when issuing firms are large relative to repurchasing firms. While our strongest results are for portfolios based on book‐to‐market (i.e., HML ), size (i.e., SMB ), and industry, our approach is also useful for forecasting factor returns associated with distress, payout policy, and profitability.